2021
DOI: 10.3390/nu13124409
|View full text |Cite
|
Sign up to set email alerts
|

Goji Berry Intake Increases Macular Pigment Optical Density in Healthy Adults: A Randomized Pilot Trial

Abstract: Age-related macular degeneration (AMD) is the third leading cause of blindness worldwide. Macular pigment optical density (MPOD), a biomarker for AMD, is a non-invasive measure to assess risk. The macula xanthophyll pigments lutein (L) and zeaxanthin (Z) protect against blue light and provide oxidant defense, which can be indexed by MPOD. This study examined the effects of Z-rich goji berry intake on MPOD and skin carotenoids in healthy individuals. A randomized, unmasked, parallel-arm study was conducted with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…14 Human trials support that daily supplements of L. barbarum berry increase macular pigment and delay the progress of AMD in healthy middle-aged persons. [15][16][17] In vitro studies indicate that L. barbarum berry protects ARPE-19 cells from oxidative stress-induced apoptosis. 18 These findings indicate that L. barbarum berry is beneficial for AMD.…”
Section: Introductionmentioning
confidence: 99%
“…14 Human trials support that daily supplements of L. barbarum berry increase macular pigment and delay the progress of AMD in healthy middle-aged persons. [15][16][17] In vitro studies indicate that L. barbarum berry protects ARPE-19 cells from oxidative stress-induced apoptosis. 18 These findings indicate that L. barbarum berry is beneficial for AMD.…”
Section: Introductionmentioning
confidence: 99%
“…AMD is a leading cause of central visual impairment globally [ 155 ]. A recent population-based study showed that goji berries might help prevent or delay the development of AMD [ 125 , 126 , 127 ]. The main pathological changes associated with AMD are the damage of RPE cells, retinal warts and atrophy, and the obstruction of the choroidal capillary.…”
Section: Protective Role Of Lbps In Oxidative Stress-related Ocular D...mentioning
confidence: 99%
“…Based on this result, goji berry has been proposed as an inexpensive, effective, and safe food dietary strategy to increase plasma zeaxanthin concentration [ 81 ]. A recent study showed that 90 days of goji berry consumption was accompanied by an increase in macular pigment optical density, a marker of age-related macular degeneration in healthy, middle-aged adults [ 96 ]. Other studies demonstrated that dietary intervention with a proprietary milk-based formulation of goji berry (13.7 g/day), with enhancing zeaxanthin bioavailability [ 98 ], for 90 days, increases plasma zeaxanthin and improves antioxidant capacity and macular characteristics [ 87 ], as well as enhancing the immune system in healthy elderly subjects [ 88 ].…”
Section: Health Benefits and Side Effects Of Goji Berry Consumptionmentioning
confidence: 99%